A physics-informed transformer framework for multi-step 6-DOF motion prediction of distressed vessels - Yingjie Yu; Xiufeng Zhang; Siming Zhang; Mingjie Li (Ocean Engineering, 2026)

Increased microbiological risks caused by extreme precipitation in a drinking water system in mountainous area: From source to tap - Xinyan Xiao; Chen Cheng; Xiuxiu Wang; Ziqi Luo; Lihua Li; Siming Hu; Dongmei Zhu; Mingbao Feng; Chengsong Ye; Xin Yu (Journal of Hazardous Materials, 2026)

Scalable fabrication of ultrathin LiIn@Cu composite anodes via roll-to-roll dip coating for high-energy-density batteries - Qihang Zhang; Anli Wang; Yifei Chen; Zihan Lin; Changyi Dong; Qiang Lu; Jixian Lv; Weike Yu; Siming Yang; Xiaoqun Qi; Jia Li; Fei Shen; et al. (Chemical Engineering Journal, 2026)

Cumulative impact forces of rock avalanches on bridge piers: role of particle-size distribution and impulse overlap - Liping Guo; Siming He; Yuntao Jin; Xiao Yu; Yuhang Lei; Bo Xiang (Landslides, 2026)

Changes in ginseng wine flavor characteristics during fermentation with Saccharomyces cerevisiae - Shen Yao; Yang Li; Xianwei Zeng; Yuan Cui; Zhaolian Li; Meichen Liu; Daqing Zhao; Shiting Yu; Siming Wang (Food Chemistry, 2026)

Fragmentation induced mobility and runout mechanism of large rock avalanche: A case study on the Tibetan Plateau, China - Xiong Tang; Lei Zhu; Siming He; Michel Jaboyedoff; Zenan Huo; Running Hou; Di Wang; Yu Luo (Engineering Geology, 2026)

3D MPM simulation of the coseismic Daguangbao landslide with a state-dependent frictional weakening model - Xiaoqin Lei; Lei Zhu; Siming He; Xinpo Li; Liu Ming; Yu Luo (Landslides, 2026)

Effects of isolation layer on the segmental tunnel transiting soil-rock strata under transverse excitation - Yong Yuan; Siming Li; Mingqing Xiao; Haitao Yu; Roberto Cudmani (Soil Dynamics and Earthquake Engineering, 2026)

Purifying or polluting? Tracing membrane-based microplastics release for long-term drinking water safety - Shunyao Yu; Siming Xie; Yaya Zhu; Wei Wang; Zhitong Liu; Xian Bao; Jun Ma (Water Research, 2026)

Segmental tunnel with isolation layer in soil-rock transition under longitudinal excitation: experimental and numerical investigation - Siming Li; Yong Yuan; Roberto Cudmani; Jinghua Zhang; Mingqing Xiao; Haitao Yu (Transportation Geotechnics, 2026)

Seismic response of segmental tunnel in soil-rock strata under longitudinal excitation: experimental and numerical analysis - Siming Li; Yong Yuan; Haitao Yu; Jinghua Zhang; Mingqing Xiao; Roberto Cudmani (Soil Dynamics and Earthquake Engineering, 2026)

Non-thermal preparation, component identification, and in vivo antioxidant activity mechanism exploration of polyphenols and derivatives from Ananas comosus (L.) flesh - Quancen Lee; Lijuan Xu; Weiguang Zhou; Ming Yu; Di Zeng; Siming Zhu (Food Research International, 2025)

Interaction mechanism and structure-activity relationship of hesperidin, methyl hesperidin and hesperidin methyl chalcone with ovalbumin: A comparative study - Xuefei Wen; Xinpeng Li; Siming Zhu; Liang Chen; Zhendong Wang; Ming Yu; Zhanhua Deng (Food Chemistry, 2025)

Facile upcycling of color-mixed polyethylene terephthalate-based textile waste via mild solvolysis with a natural aromatic solvent - Yue Zhu; Jindan Tang; Siming Zhu; Yu Liu; Liping Lou; Qingqing Mei (Chemical Engineering Journal, 2025)

A galacturonan from sea buckthorn (Hippophae rhamnoides L.) berry modulates dyslipidemia by promoting hepatic lipolysis and mitochondrial oxidation - Yunpeng Sun; Weifeng Ni; Dongyi Wang; Jixiang Ren; Daqing Zhao; Shiting Yu; Shichao Liu; Shaojie Zhang; Siming Wang; Weinan Wang; Meichen Liu (Carbohydrate Polymers, 2025)

Isolation and identification of native microalgae from the Yellow River Delta: A dual-focus study on the tolerance assessment of microalgae and their growth enhancement on Sesbania cannabina under saline-alkali stress - Xiao Yu; Siming Li; Jiahao Liang; Shenkun Liu; Yinchu Wang; Jianchao Yang; Chenggang Ren; Chunli Ji; Hongli Cui; Song Qin (Algal Research, 2025)

The impact of school activity space layout on children's physical activity levels during recess: An agent -based model computational approach - Jiameng Cui; Xue Meng; Siming Qi; Junwen Fan; Wenxuan Yu; Hongxing Liu; Xiang Wang; Yu Zhang (Building and Environment, 2025)

Analysis of sediment re-formation factors after ginseng beverage clarification based on XGBoost machine learning algorithm - Jiabao Feng; Yuan Cui; Chunyan Jiang; Xueyuan Bai; Daqing Zhao; Meichen Liu; Zhengqi Dong; Shiting Yu; Siming Wang (Food Chemistry, 2025)

Experimental Investigation of Seismic Signal Characteristics Arising from Basal Stress Fluctuations in Granular Flow - Xiao Yu; Zheng Chen; Siming He; Wei Liu; Dongpo Wang (Rock Mechanics and Rock Engineering, 2025)

Enhanced damage modelling of steel wire ring nets subjected to repeated rockfall impacts - Liping Guo; Zhixiang Yu; Siming He; Yuntao Jin; Jihao Jian (Computers and Geotechnics, 2024)

Biochar derived from animal and plant facilitates synergistic transformation of heavy metals and phosphorus in sewage sludge composting - Meihua Zhao; Siming Zhong; Xiasong Zhou; Zhen Yu (Environmental Pollution, 2024)

Influence of group VIB metals introduced into zeolite on the adsorption performance of VOCs in cooking oil fumes - Honghong Yi; Siming Guo; Yuting Yuan; Qingjun Yu; Fengshi Meng; Wenjing Wu; Shunzheng Zhao; Ya Wang; Xiaolong Tang (Chemical Engineering Journal, 2024)

Investigating the dynamic process of a rock avalanche through an MLS-MPM simulation incorporated with a nonlocal μ(I) rheology model - Shuxi Zhao; Siming He; Xinpo Li; Gianvito Scaringi; Yang Liu; Yu Deng (Landslides, 2024)

Do E-governance, mineral resources, and policy stringency facilitate economic growth in selected resource-rich countries - Wenjun Wu; Zhilong Zhao; Siming Yu; Minyuan Zhang (Resources Policy, 2024)

Mechanism of the solubility increase of rice protein-ovalbumin co-assembly and its great potential as an emulsifier in high internal phase emulsion - Zufu Song; Siming Zhao; Xiaoli Zhang; Qing Zhang; Yu Han; Meng Niu; Yan Xu (Journal of Cereal Science, 2024)

Anticancer effect of hUC-MSC-derived exosome-mediated delivery of PMO-miR-146b-5p in colorectal cancer - Siming Yu; Ran Liao; Lu Bai; Madi Guo; Yu Zhang; Yumin Zhang; Qi Yang; Yushuai Song; Zhiwei Li; Qingwei Meng; Shubin Wang; Xiaoyi Huang (Drug Delivery and Translational Research, 2024)
Antisense oligonucleotide (ASO) is a novel therapeutic platform for targeted cancer therapy. Previously, we have demonstrated that miR-146b-5p plays an important role in colorectal cancer progression. However, a safe and effective strategy for delivery of an ASO to its targeted RNA remains as a major hurdle in translational advances. Human umbilical cord mesenchymal cell (hUC-MSC)–derived exosomes were used as vehicles to deliver an anti-miR-146b-5p ASO (PMO-146b). PMO-146b was assembled onto the surface of exosomes (e) through covalent conjugation to an anchor peptide CP05 (P) that recognized an exosomal surface marker, CD63, forming a complex named ePPMO-146b. After ePPMO-146b treatment, cell proliferation, uptake ability, and migration assays were performed, and epithelial-mesenchymal transition progression was evaluated in vitro. A mouse xenograft model was used to determine the antitumor effect and distribution of ePPMO-146b in vivo. ePPMO-146b was taken up by SW620 cells and effectively inhibited cell proliferation and migration . The conjugate also exerted antitumor efficacy in a xenograft mouse model of colon cancer by systematic administration, where PPMO-146b was enriched in tumor tissue. Our study highlights the potential of hUC-MSC-derived exosomes anchored with PPMO-146b as a novel safe and effective approach for PMO backboned ASO delivery. Graphical Abstract Schematic illustration of the preparation of an exosomal anchor peptide (CP05)-PMO that conjugately binds to exosomes from hUC-MSCs (ePPMO-146b) and the antitumor effect of ePPMO-146b in CRC, which occurs through the inhibition of Smad signaling and epithelial–mesenchymal transition.

The influence of biochar from animal and plant on the transformation of phosphorus during paper mill sludge composting - Siming Zhong; Zhen Yu; Xiaoming Liu; Meihua Zhao; Hongwei Rong (Environmental Science and Pollution Research, 2024)

A new Cd(II) Complex: Fluorescence Performances, Loading with Budesonide-hydrogels on Pediatric Asthma and Molecular Docking - Lu Luo; Siming Gong; Lin Lei; Xin Yu; Shimin Zhong (Journal of Fluorescence, 2024)

Biodegradable copper peroxide decorated hollow polydopamine nanocomposite as effective chloroperoxidase delivery carrier for enhancing enzyme dynamic therapy via self-activated cascade reactions - Weiwei Wu; Yan Yang; Yu Zhang; Yina Zeng; Zhuoying Liang; Xiling Song; Yadong Huang; Wei Xue; Siming Yu (Chemical Engineering Journal, 2024)

Assessing the Efficiency of Thermochemical Pressurization in the Jiweishan Rockslide - Yu Deng; Xuanmei Fan; Gianvito Scaringi; Dongpo Wang; Siming He (Rock Mechanics and Rock Engineering, 2024)

Research progress on the adsorption of sulfocompounds in flue gas - Siming Guo; Qingjun Yu; Shunzheng Zhao; Xiaolong Tang; Ya Wang; Yiming Ma; Yuhan Long; Honghong Yi (Chemical Engineering Journal, 2023)

Creep-to-Runout Transition of Large Landslides Controlled by Frictional Velocity Strengthening and Weakening (Vajont 1963, Italy) - Huanhuan Zhang; Siming He; Wei Liu; Yu Deng; Wei Hu (Rock Mechanics and Rock Engineering, 2023)

Shaking table test on a segmental tunnel crossing soil-rock interface under transverse sinusoidal excitations - Siming Li; Yong Yuan; Haitao Yu; Jinghua Zhang; Roberto Cudmani (Tunnelling and Underground Space Technology, 2023)

Role of mining waste trade on green development in China: Policy implications for circular economy - Siming Yu; Xun Wang; Jiaming Liu; Fang Wei (Resources Policy, 2023)

Glutathione-Responsive Sulfur Dioxide-Releasing Dendronized Chitooligosaccharide Polymer for Effective Treatment of Multidrug-Resistant Bacterial Infection - Haitao Yu; Jiejiao Liu; Qianwen Lin; Jun Liu; Siming Yu; Pinghua Sun; Jing Lin (Chemical Engineering Journal, 2023)

The impact of GmTSA and GmALS on soybean salt tolerance: uncovering the molecular landscape of amino acid and secondary metabolism pathways - Minghao Sun; Siming Wei; Jiarui Liu; Luyao Wang; Yu Zhang; Limin Hu; Jingxi Piao; Zhao Liang; Hongwei Jiang; Dawei Xin; Ying Zhao; Qingshan Chen; et al. (Theoretical and Applied Genetics, 2023)

Emissions of formaldehyde and nitrogen dioxide from liquefied petroleum gas combustion - Jin Ye; Siming Shi; Tao Yu; Cong Liu; Jingguang Li; Zhen Ding; Zhijiong Huang; Hua Qian (Process Safety and Environmental Protection, 2023)

Russia-Ukraine war perspective of natural resources extraction: A conflict with impact on sustainable development - Shouwen Wang; Lijie Xu; Siming Yu; Siyao Wang (Resources Policy, 2023)

Resource curse and green growth in China: Role of energy transitions under COP26 declarations - Siming Yu; Kang Wan; Cheng Cai; Lingli Xu; Tuanjie Zhao (Resources Policy, 2023)

Isoalantolactone relieves depression-like behaviors in mice after chronic social defeat stress via the gut-brain axis - Siming Wang; Qihan Cai; Lu Xu; Yanan Sun; Mengmeng Wang; Yu Wang; Lili Zhang; Keqing Li; Zhiyu Ni (Psychopharmacology, 2023)
Rationale The management of depression continues to be challenging despite the variety of available antidepressants. Herbal medicines are used in many cultures but lack stringent testing to understand their efficacy and mechanism of action. Isoalantolactone (LAT) from Elecampane ( Inula helenium ) improved the chronic social defeat stress (CSDS)-induced anhedonia-like phenotype in mice comparable to fluoxetine, a selective serotonin reuptake inhibitor (SSRI). Objectives Compare the effects of LAT and fluoxetine on depression-like behaviors in mice exposed to CSDS. Result The CSDS-induced decrease in protein expression of postsynaptic density (PSD95), brain derived neurotrophic factor (BDNF), and glutamate receptor subunit-1 (GluA1) in the prefrontal cortex was restored by LAT. LAT showed robust anti-inflammatory activity and can lessen the increase in IL-6 and TNF-α caused by CSDS. CSDS altered the gut microbiota at the taxonomic level, resulting in significant changes in α- and β-diversity. LAT treatment reestablished the bacterial abundance and diversity and increased the production of butyric acid in the gut that was inhibited by CSDS. The levels of butyric acid were negatively correlated with the abundance of Bacteroidetes , and positively correlated with those of Proteobacteria and Firmicutes across all treatment groups. Conclusions The current data suggest that, similar to fluoxetine, LAT show antidepressant-like effects in mice exposed to CSDS through the modulation of the gut-brain axis.

The in-situ dextran produced in rice protein yogurt: Effect on viscosity and structural characteristics - Yu Lu; Caihua Jia; Meng Niu; Yan Xu; Siming Zhao (Carbohydrate Polymers, 2023)

Effect of particle crushing– and thermally induced pressurization on rockslide mobility - Yu Deng; Xuanmei Fan; Gianvito Scaringi; Dongpo Wang; Siming He (Landslides, 2023)

Local site effect of soil-rock ground: 1-g shaking table test - Yong Yuan; Siming Li; Haitao Yu; Mingqing Xiao; Ruohan Li; Ruozhou Li (Bulletin of Earthquake Engineering, 2023)

Integration of anaerobic digestion with heat Pump: Machine learning-based technical and environmental assessment - Zahra Hajabdollahi Ouderji; Rohit Gupta; Andrew Mckeown; Zhibin Yu; Cindy Smith; William Sloan; Siming You (Bioresource Technology, 2023)

Characteristics and failure mechanism of the 2018 Yanyuan landslide in Sichuan, China - Lei Zhu; Yu Deng; Siming He (Landslides, 2019)

Impact protection of bridge piers against rockfall - Siming He; Shuaixing Yan; Yu Deng; Wei Liu (Bulletin of Engineering Geology and the Environment, 2019)

Source characteristics and dynamics of the October 2018 Baige landslide revealed by broadband seismograms - Zhen Zhang; Siming He; Wei Liu; Heng Liang; Shuaixing Yan; Yu Deng; Xiuqiang Bai; Zheng Chen (Landslides, 2019)

Dynamic process simulation of rainfall-induced Sanxicun landslide based on a thermo-poro-elastic approach - Yu Luo; Wei Liu; Siming He; Jiang Yuanjun; Xiaoqing Lei (Natural Hazards, 2018)

CD200Fc reduces TLR4-mediated inflammatory responses in LPS-induced rat primary microglial cells via inhibition of the NF-κB pathway - Li Jiang; Fan Xu; Wenjing He; Lifei Chen; Haibin Zhong; Yu Wu; Siming Zeng; Li Li; Min Li (Inflammation Research, 2016)

Molecular cloning, recombinant expression, and antifungal functional characterization of the lipid transfer protein from Panax ginseng - Kexin Cai; Jiawen Wang; Min Wang; Hui Zhang; Siming Wang; Yu Zhao (Biotechnology Letters, 2016)

CspE is Overproduced by Temperature Downshift in the Acinetobacter johnsonii DBP-3 - Dan Su; Linlin Hao; Fuwang Chen; Siming Li; Ahmed Mohamed Abdelrahman; Yu Zhang; Hao Yu; Songcai Liu; Mingtang Li (Current Microbiology, 2016)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

Fibroblast growth factor (FGF21) protects mouse liver against d-galactose-induced oxidative stress and apoptosis via activating Nrf2 and PI3K/Akt pathways - Yinhang Yu; Fuliang Bai; Yaonan Liu; Yongbi Yang; Qingyan Yuan; Dehua Zou; Susu Qu; Guiyou Tian; Liying Song; Tong Zhang; Siming Li; YunYe Liu; et al. (Molecular and Cellular Biochemistry, 2015)

Up-regulation of SKIP relates to retinal ganglion cells apoptosis after optic nerve crush in vivo - Yu Wu; Fan Xu; Hui Huang; Lifei Chen; Meidan Wen; Li Jiang; Lu Lu; Li Li; Di Song; Siming Zeng; Li Li; Min Li (Journal of Molecular Histology, 2014)

Upregulation of Gem relates to retinal ganglion cells apoptosis after optic nerve crush in adult rats - Fan Xu; Hui Huang; Yu Wu; Lu Lu; Li Jiang; Lifei Chen; Siming Zeng; Li Li; Min Li (Journal of Molecular Histology, 2014)

Comparative analysis of differentially expressed genes in Sika deer antler at different stages - Yu Zhao; Baojin Yao; Mei Zhang; Siming Wang; Hui Zhang; Wei Xiao (Molecular Biology Reports, 2013)

Study on the rainfall and aftershock threshold for debris flow of post-earthquake - Siming He; Dexin Li; Yong Wu; Yu Luo (Journal of Mountain Science, 2011)

Failure mechanisms of post-earthquake bedrock landslides in response to rainfall infiltration - Yong Wu; Siming He; Yu Luo; Xinpo Li (Journal of Mountain Science, 2011)

Discrete element modeling of debris avalanche impact on retaining walls - Xinpo Li; Siming He; Yu Luo; Yong Wu (Journal of Mountain Science, 2010)